A work study on Samway Corporation - Cuevas, Sabrina Marie; Macalinao, Laura Karen Grace P.; So, Sheryl Lyn M. (Diliman, Quezon City College of Engineering, 2000)
The BG Samson Enterprise is composed of sub-companies, which caters to a wide range of products from things such as food and beverages to chemicals for personal care and autocare products. It is basically a household organization and practices batch production. One of the companies of this household enterprise is SAMWAY Corporation, the company which is responsible for manufacturing the autocare products. This project aims to study the present situations of the company and develop a new system in order to improve efficiency in its production. This includes defining the present situations of the company, by gathering relevant data through observations, interviews and applying different tools in workstudy. Such tools include work measurement techniques, SLP, S&P and many more. After all data has been gathered, analysis takes place to determine the different problems of the company that affects performance and efficiency of their methods. The Kepner and Tregoe Approach was used as a framework for problem analysis. Tools such as, Streamline Diagnostic Chart and Ishikawa Diagrams, were applied respectively to determine the main problems and the causes of each. After all these tools were employed, it was discovered that Lack of Supervision and Poor Facility Layout contributed most problems to the company. Two alternatives were generated for each main problem. For Lack of Supervision, it was proposed that (1) standard rules and regulations should be made or an (2) additional supervisor should be hired. For Poor Facility Layout, (1) a storage room and a multipurpose cabinet should be built in order to maximize space or perhaps (2) rearrangement of the workstations should be made to utilize flow of operations. After much deliberation, and evaluation through cost analysis, alternative 2 was chosen for Lack of Supervision and alternative 2 also for Poor Facility Layout
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis